Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To determine which given expression is equal to [tex]\(5^0 + 2^1 \)[/tex], let’s evaluate each option step-by-step.
First, calculate [tex]\(5^0 + 2^1\)[/tex]:
- [tex]\(5^0 = 1\)[/tex] because any number raised to the power of 0 is 1.
- [tex]\(2^1 = 2\)[/tex] because 2 raised to the power of 1 is 2.
Thus, [tex]\(5^0 + 2^1 = 1 + 2 = 3\)[/tex].
Now, compare this value (which is 3) to each given expression:
1. Evaluate [tex]\(6^0 - 6^1\)[/tex]:
- [tex]\(6^0 = 1\)[/tex]
- [tex]\(6^1 = 6\)[/tex]
Thus, [tex]\(6^0 - 6^1 = 1 - 6 = -5\)[/tex].
2. Evaluate [tex]\(6^0 - 3^0\)[/tex]:
- [tex]\(6^0 = 1\)[/tex]
- [tex]\(3^0 = 1\)[/tex]
Thus, [tex]\(6^0 - 3^0 = 1 - 1 = 0\)[/tex].
3. Evaluate [tex]\(2^0 + 2^1\)[/tex]:
- [tex]\(2^0 = 1\)[/tex]
- [tex]\(2^1 = 2\)[/tex]
Thus, [tex]\(2^0 + 2^1 = 1 + 2 = 3\)[/tex].
4. Evaluate [tex]\(2^0 \$_1^1\)[/tex]:
- The expression [tex]\(2^0 \$_1^1\)[/tex] isn’t clearly valid as it contains an unspecified operation ($).
From these evaluations, the expression [tex]\(2^0 + 2^1\)[/tex] equals 3.
Therefore, the correct answer is:
[tex]\[ \boxed{2^0 + 2^1} \][/tex]
First, calculate [tex]\(5^0 + 2^1\)[/tex]:
- [tex]\(5^0 = 1\)[/tex] because any number raised to the power of 0 is 1.
- [tex]\(2^1 = 2\)[/tex] because 2 raised to the power of 1 is 2.
Thus, [tex]\(5^0 + 2^1 = 1 + 2 = 3\)[/tex].
Now, compare this value (which is 3) to each given expression:
1. Evaluate [tex]\(6^0 - 6^1\)[/tex]:
- [tex]\(6^0 = 1\)[/tex]
- [tex]\(6^1 = 6\)[/tex]
Thus, [tex]\(6^0 - 6^1 = 1 - 6 = -5\)[/tex].
2. Evaluate [tex]\(6^0 - 3^0\)[/tex]:
- [tex]\(6^0 = 1\)[/tex]
- [tex]\(3^0 = 1\)[/tex]
Thus, [tex]\(6^0 - 3^0 = 1 - 1 = 0\)[/tex].
3. Evaluate [tex]\(2^0 + 2^1\)[/tex]:
- [tex]\(2^0 = 1\)[/tex]
- [tex]\(2^1 = 2\)[/tex]
Thus, [tex]\(2^0 + 2^1 = 1 + 2 = 3\)[/tex].
4. Evaluate [tex]\(2^0 \$_1^1\)[/tex]:
- The expression [tex]\(2^0 \$_1^1\)[/tex] isn’t clearly valid as it contains an unspecified operation ($).
From these evaluations, the expression [tex]\(2^0 + 2^1\)[/tex] equals 3.
Therefore, the correct answer is:
[tex]\[ \boxed{2^0 + 2^1} \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.